Implementing a Family Education Curriculum to Enhance Parental Roles in Character-Based Parenting: A Case Study at SMP Bisnis Aya Sophia Islamic School - Ahmad Khori; Wakhida Nurhayati; Otisia Arinindyah; Zawirrahmi Zawirrahmi; Shofiyullah Shofiyullah (Yayasan Aya Sophia Indonesia, 2025)
This study aims to analyze the implementation of the Family Education Curriculum as a strategic effort to increase parental involvement as school partners in character education. This study used a naturalistic qualitative approach with a single case study design conducted at Aya Sophia Islamic School Business Junior High School, Tangerang. Data collection techniques included observation, in-depth interviews and documentation, with analysis using the Miles and Huberman model. The results showed that curriculum planning was carried out contextually through the preparation of modules based on Islamic values and national character, program socialization, and cultural content adaptation. Program implementation is facilitated by a participatory organizational structure, face-to-face and online parent training, and community-based parenting mentoring. Formative and summative evaluations indicated a transformation of parenting from an authoritarian approach to a religious democratic model, characterized by the strengthening of affective closeness, moral exemplification, and the integration of Islamic spirituality in parenting. The findings reinforce the importance of value synergy between school and family and the need for adaptive replication of similar curricula in other contexts.